2021
DOI: 10.3390/ma14164350
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sensing Properties of Fly Ash Geopolymer Doped with Carbon Black under Compression

Abstract: The development of smart materials is a basic prerequisite for the development of new technologies enabling the continuous non-destructive diagnostic analysis of building structures. Within this framework, the piezoresistive behavior of fly ash geopolymer with added carbon black under compression was studied. Prepared cubic specimens were doped with 0.5, 1 and 2% carbon black and embedded with four copper electrodes. In order to obtain a complex characterization during compressive loading, the electrical resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The piezoresistivity of the inorganic polymer was significantly higher than that reported in prior studies of inorganic polymers under cyclic loading. Inorganic polymers without conductive additives have FCR below 1% when measured with direct current under cyclic loading. , The use of alternating current increases the detectable FCR by a factor of 10, opening the door to future use of inorganic polymers as self-sensing materials. Portland cement is known to have negligible FCR under cyclic loading conditions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The piezoresistivity of the inorganic polymer was significantly higher than that reported in prior studies of inorganic polymers under cyclic loading. Inorganic polymers without conductive additives have FCR below 1% when measured with direct current under cyclic loading. , The use of alternating current increases the detectable FCR by a factor of 10, opening the door to future use of inorganic polymers as self-sensing materials. Portland cement is known to have negligible FCR under cyclic loading conditions …”
Section: Resultsmentioning
confidence: 99%
“…Generally, they exhibit high mechanical properties and are considered a low-cost and environmentally friendly alternative to Portland cement because they can be synthesized from industrial byproducts that are rich in aluminum and silicon oxides, such as blast furnace slag and coal fly ash . Alkali-activated inorganic polymers have been investigated as a matrix material for self-sensing composites with conductive additives. However, their intrinsic piezoresistivity was found to be negligible with conventional measurement methods.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to geopolymer concretes, at the moment in scientific publications, topics related to the piezo-resistant behavior of geopolymer concretes under various deformations and the development of technologies that allow using this factor for the continuous monitoring of the state of building structures are gaining popularity. The authors of [ 200 ] carried out a work devoted to the study of the piezoresistance behavior of a geopolymer material based on FA with the addition of carbon black during compression. Prototypes were made in the form of cubes with the addition of carbon black in the amount of 0.5%, 1% and 2%, in which four copper electrodes were embedded.…”
Section: Modern Trends and Innovations In The Field Of Research Of Ge...mentioning
confidence: 99%
“…Fourier-transform infrared (FTIR) analysis revealed that the original GO undergoes a reduction in the course of geopolymers' processing. Cecílie Mizerová et al (7) show that the examination of compressive strain and acoustic emission data revealed that fly ash geopolymer lacks the necessary rigidity. Under loading conditions, it experiences permanent deformations, attributed in part to the creation of micro defects in the binder's structure and partly to the transition from quasi-brittle to more ductile properties with the introduction of carbon black.…”
Section: Introductionmentioning
confidence: 99%
“…Its inclusion in the blend not only enhances the sustainability of the research but also significantly contributes to conferring self-sensing capabilities upon the concrete. (12,13) Type F fly ash encompasses diverse chemical elements capable of influencing the electrical properties of concrete, (7) thereby establishing its indispensability in the development of self-sensing abilities. The incorporation of Reclaimed Salud, Ciencia y Tecnología -Serie de Conferencias.…”
Section: Introductionmentioning
confidence: 99%